"Distant Participation" and Youth Political Attitudes: Evidence from a Natural Experiment. (12th June 2020) - Wong, Stan Hok‐Wui; Wong, Mathew Y. H.
Abstract : Objective: In this article, we explore the seldom studied concept of "distant participation, " defined as the experience of social movements (such as receiving information from online media) from overseas. Online media may affect people's political attitudes, but how people use online media is also contingent upon their political attitudes. Method: We take advantage of a natural experiment to deal with this endogenous selection problem. Our treatment group consists of college students who happened to join a short‐term overseas exchange program during the Umbrella Movement, which had an unexpectedly large turnout in Hong Kong. These students had a different mode of participation in the event from their peers physically in Hong Kong. The experience, including intensive exposure to online media, changed their media consumption habits, and hence their political attitudes. Results: We find that the treatment group is more likely to report using online media to obtain news. They also have a stronger sense of political efficacy and significantly weaker national identity. We, however, find no significant difference between the treatment and control groups regarding civic and political participation. Conclusion: This study provides a rare contribution to the study of the effect of online media by tackling the problem of selection. The concept of distant participation should also be given more attention given the ease of population flow and technological advancement nowadays.